Two knitted mittens from a 17th century Dutch shipwreck - Willemsen, Annemarieke (Archaeological Textiles Review, 2018)
Two knitted mittens (but not likely a pair) were found in the same shipwreck, known as Burgzand Noord 8, in the Dutch Wadden Sea off the island of Texel. They were knitted round, narrowing at the wrist and tips of the thumbs. One of the mittens was dyed blue according to chromatographic analysis. Both show traces of wear and spots of tar, which indicate they were used on board. Coins corroded on to the blue mitten indicate that it was close to money in the officers’ quarters where it was found at the time of the wreck. The wool mittens were with other wool clothing, which suggests that the ship was lost in winter, while other finds pinpoint it to an infamous December storm of 1660. These mittens are two rare examples of knitted garments in the Netherlands, where gloves and mittens made from cloth seem to have been more usual.